Research of cyclic properties of permutations, realized with the simplest regular OCCM - Ianovska, Olena (Видавництво Львівської політехніки, 2012)
The paper is devoted to experimenrtal determination of regularities of cyclic paths of complete and incomplete permutations, realized by means of the simplest regular OCCM. The paper is based on results obtained before and it specifies them.
Keywords: permutations; logical network; regular structure; cyclic properties; application examples